The 3cs- CULTURE- CONFLICT- CHANGE, Educational Organizations Downfall If Unaddressed: A Reflective Paper - J. Grant Coke Monique (Journal of Human Psychology, 2022)
This reflective paper argues that culture, conflict, and change (the “3Cs”) shape educational organizations’ success. It offers examples and leadership practices to diagnose issues and steer constructive transformation.
Keywords: Culture